Brachman de lange syndrome - Leena Verma; Sidhi Passi; Krishan Gauba (Wolters Kluwer Medknow Publications, 2010)
Brachman de Lange syndrome or Cornelia de Lange syndrome (CdLS) is a genetic disorder which can lead to severe developmental anomalies. It affects both the physical and intellectual development of a child. It is characterized by skeletal, craniofacial deformities, gastrointestinal and cardiac malformations. This syndrome is of rare occurrence and affects between 1/10,000 and 1/60,000 neonates. Diagnosis is based on the characteristic phenotype, in particular, a striking facial appearance, prenatal and postnatal growth retardation, various skeletal abnormalities, hypertrichosis, and developmental delay. Here, we present the case of a 13-year-old patient, with micrognathia, delayed eruption, multiple carious teeth, missing teeth and periodontal problems together, which had never been reported before. The father was also found to have the same missing teeth as the girl child.